Measuring and Explaining Stalled Gentrification in Newark, New Jersey: The Role of Racial Politics. Issue 6 (November 2022) - Morel, Domingo; Drake Rodriguez, Akira; Sidney, Mara; Garay, Nakeefa Bernard; Straub, Adam
Gentrification research focuses on timing and variation; how the racial makeup of cities and neighborhoods influences its extent; and the policies that foster or combat it. Most examines places with continuing or recent gentrification and majority-White leadership, such as New York City and San Francisco. We build on this by analyzing a majority-Black city where fear of gentrification is increasing, but gentrification is not widespread. To analyze Newark, NJ, a city with longstanding Black leadership, we adapt widely used measures to show that gentrification started but stalled during the 2000s. We examine whether policies explain this, and whether the racial politics of the city's majority-Black population and leadership play a role. Our findings suggest that mayoral administrations took similar, growth-driven approaches, except that the current mayor is the first to place "fighting gentrification" onto the agenda. We end by considering how the politics of race shape the politics of gentrification.